(untitled) (SciELO Preprints, 2022)
The “Coleção de Flebotomíneos” (FIOCRUZ/COLFLEB) held at Fiocruz Minas is a curated biological collection comprised of approximately 80,000 individual specimens of 370 species of sand flies (Diptera: Psychodidae, Phlebotominae) mostly from the Americas collected over the last 80 years by entomologists interested in understanding and controlling the vector-borne disease leishmaniases. Since 2010, the metadata of each of the individual biological specimens held in FIOCRUZ/COLFLEB, including the back catalogue of those deposited in previous decades, has been digitized. Here, our resulting electronic catalogue, containing records for 72,624 of the specimens, including all of the available provenance information associated with each of them, is published online through the speciesLink network <http://www.splink.org.br/search?collectioncode=FIOCRUZ11COLFLEB&group=animais&lang=pt&action=openform> and the Sistema de Informação sobre a Biodiversidade Brasileira (SiBBr) <http://ipt.fiocruz.br/ipt/resource?r=fiocruz_colfleb>.